Colonization of freshwater biofilms by nitrifying bacteria from activated sludge. Issue 1 (2nd April 2013) - Mußmann, Marc; Ribot, Miquel; von, Daniel; Merbt, Stephanie N.; Augspurger, Clemens; Karwautz, Clemens; Winkel, Matthias; Battin, Tom J.; Martí, Eugènia; Daims, Holger
Abstract Effluents from wastewater treatment plants (WWTPs) containing micro‐organisms and residual nitrogen can stimulate nitrification in freshwater streams. We hypothesized that different ammonia‐oxidizing (AOB) and nitrite‐oxidizing (NOB) bacteria present in WWTP effluents differ in their potential to colonize biofilms in the receiving streams. In an experimental approach, we monitored biofilm colonization by nitrifiers in ammonium‐ or nitrite‐fed microcosm flumes after inoculation with activated sludge. In a field study, we compared the nitrifier communities in a full‐scale WWTP and in epilithic biofilms downstream of the WWTP outlet. Despite substantially different ammonia concentrations in the microcosms and the stream, the same nitrifiers were detected by fluorescence in situ hybridization in all biofilms. Of the diverse nitrifiers present in the WWTPs, only AOB of the Nitrosomonas oligotropha/ureae lineage and NOB of Nitrospira sublineage I colonized the natural biofilms. Analysis of the amoA gene encoding the alpha subunit of ammonia monooxygenase of AOB revealed seven identical amoA sequence types. Six of these affiliated with the N. oligotropha/ureae lineage and were shared between the WWTP and the stream biofilms, but the other shared sequence type grouped with the N. europaea/eutropha and N. communis lineage. Measured nitrification activities were high in the microcosms and the stream. Our results show that nitrifiers from WWTPs can colonize freshwater biofilms and confirm that WWTP‐affected streams are hot spots of nitrification.